The time effect of Mint and Lavender oil on nausea and vomiting of pregnancy based on Rhodes index - Azam Amzajerdi; Maryam Keshavarz; Fatemeh Sarvi; Reza Bekhradi (Mashhad University of Medical Sciences, 2022)
Introduction: Nausea and vomiting of pregnancy is a common condition which affects the health of a pregnant woman and her fetus and significantly affects the quality of life of pregnant women. Therefore, the present study was designed aimed to compare the time effect of Mint and Lavender oil on nausea and vomiting of pregnancy based on Rhodes index. Methods: This semi-experimental study was conducted in 2015-2016 on 107 pregnant women with a gestational age of 6-16 weeks who referred to the prenatal care clinic in Tehran. The subjects were divided into three groups: Mint, Lavender, and placebo) sesame oil). The participants respectively inhaled Mint, Lavender, and sesame oil twice a day (before rest in the afternoon and night sleep) for 20 minutes for one week. The mean total score of Rhodes index before and during the intervention days and the variables of this index before and on the seventh day after the intervention were compared in three groups. Data were analyzed by SPSS software (version 16) and statistical tests of analysis of variance, paired t, independent t, Kruskal-Wallis, Chi-square, Fisher's exact and analysis of variance with repeated measurements. P< 0.05 was considered statistically significant. Results: Before the intervention, there was no significant difference between the three groups in the mean total score and variables of the Rhodes index. From the fifth day after the intervention, the mean total score of the Rhodes index was significantly different between the three groups (fifth day P= 0.047, sixth day P= 0.009 and seventh day P= 0.001). The mean total score of the Rhodes index on the fifth and sixth days after the intervention was significantly lower in the Mint group than the placebo (P= 0.002 and P= 0.020, respectively). On the seventh day, the mean total score of this index was lower in the Mint and Lavender groups than the placebo group (P= 0.008 and P< 0.0001, respectively). Comparison of Rhodes index variables on the seventh day after the intervention showed that in the Mint group, the severity of nausea (P= 0.001), the frequency of nausea (P= 0.001), and the frequency of retching (P= 0.002), and in the Lavender group, the severity of nausea (P= 0.011) was less than the placebo group. Conclusion: In this study, the effect of Mint aroma on pregnancy nausea and vomiting appeared earlier than Lavender aroma. Also, according to the Rhodes index, it was effective on more variables of nausea and vomiting. Mint and Lavender aroma can be considered as a simple, accessible and uncomplicated method for reducing nausea and vomiting in pregnant women.